THE ASSESSMENT OF THE COMPLETENESS OF EDUCATIONAL CONTENT USING THE EXAMPLE OF TECHNICAL SUBJECTS - PLISCHKE, Jitka; KROPAC, Jiri (Journal of Technology and Information Education, 2013)
The text deals with the completeness of educational content, analyzes this concept especially in technical subjects. The focus of the text points to the assessment of completeness of the educational content, the possible considerations and requirements in terms of educational experience and current educational theories.
Keywords: Completeness; educational content; technical subjects; Maslow's Hierarchy of Needs